STUDY ON GENETIC DIVERSITY AND CONSERVATION OF ORCHIDS IN WONOSADI FOREST, GUNUNGKIDUL BASED ON MOLECULAR ANALYSIS - Aruni, Dian; Abdullah, Suprapty; Mahfut, .; Daryono, Budi Setiadi (2011)
Wonosadi forest is located between Dusun Duren and Dusun Sidorejo, Beji village, Ngawen, Gunungkidul. The biodiversity inside Wonosadi is protected by people around Wonosadi using local wisdom. One of the endemic biological diversity in Wonosadi is natural orchid. Conservation which is related to biodiversity were needed to maintain the existence of natural orchid in Wonosadi sustainly. Study on natural orchid in Wonosadi can be used as the database for conservation programs. In this study, genetic variation was analysed usi ng random amplified polymorphic DNA (RAPD), while viruses were detected using reverse transcript-polymerase chain reaction (RT-PCR). The results show that there were genetic diversity in the populations of natural orchid in Wonosadi. It can be concluded that the population of natural orchid in Wonosadi can be adaptive to environmental change. Genetic diversity is required for populations to evolve to cope with environmental change. It can be used as a database to develop the potential of natural orchid in Wonosadi forest. The viruses found in population of natural orchid in Wonosadi were Cymbidium mosaic virus (CyMV) and Odontoglossum ringspot virus (ORSV). Viruses existance might be recognised from the physical symptom on plant and analysis of coat protein (CP) gene using polymerase chain reaction (PCR). The research of diversity and conservation of natural orchid in Wonosadi forest ma y be used to support education for sustainable development (EfSD) concept in conservation of biological diversity. Exploration activity can be focused at area which is protected by local wisdom and involves local people. By doing this, local people may be actively included on protecting and developing biological diversity at their own comunity. Thus, it may result a sustain condition of natural resources. This research can be used in supporting and developing programs of natural orchid in Wonosadi forest in order to develop the conservation programs. Keywords : genetic diversity, natural orchid, CyMV, ORSV, conservation